Appraisal of Private Sector Involvement in Infrastructure Development in Lagos State, Nigeria - Taye, Ojuola Olasijibomi; Dada, Martin Oloruntobi (Mediterranean Journal of Social Sciences, 2012)
The need for the provision of infrastructure in any developing country cannot be overemphasized as it constitutes thebackbone of the country’s national economy. Considering the importance of infrastructure, government at all levels has oftenborne the full responsibility of providing infrastructure via dependence on loans and credits from financial institutions notrecognizing the fact that the investment requirement for the infrastructure deficit is such that cannot possibly be met by relying onthe public sector to boost public investment without increasing public borrowing. To this end, this research sought to appraise theinvolvement of the private sector in infrastructure development in Lagos State through the use of the public-private-partnership(PPP). Questions were asked to investigate the level of awareness about and the use of various models or variants of PPPs.105 questionnaires were administered on professional firms/agencies (construction consultants, contractors, financinginstitutions and concessionaires) that have been or are involved in PPP projects in Lagos state. 66 responses were obtained.The data was subjected to both descriptive and inferential statistical analysis. The results of the study indicate that the levels ofawareness of private sector involvement in infrastructure development using PPPs as well as the areas of involvement were notsignificant. It is recommended that government should put more efforts to improve the level of awareness on the involvement ofthe private sector participation in the provision of infrastructure through public enlightenment both locally and internationallystating the benefits that are obtainable both for citizens and investors.